2008
DOI: 10.1016/j.pain.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Altered cerebral response to noxious heat stimulation in patients with somatoform pain disorder

Abstract: Idiopathic chronic pain conditions with a mismatch between anatomical abnormalities and symptoms can be categorized as somatoform pain disorder according to the DSM-IV criteria. A dysfunction of pain processing circuits has been suggested as one underlying pathophysiological factor. There is accumulating evidence for a crucial role of affect regulating brain structures such as the medial frontal cortex in this context. We investigated the cerebral processing of noxious heat stimuli as objective marker for pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
63
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 51 publications
12
63
0
4
Order By: Relevance
“…For example, noxious heat led to higher blood oxygen-level dependent signalling in the insula and parahippocampal gyrus, while medial prefrontal cortex activity was reduced. 58 Reduced insula and amygdala activity was observed during emotional empathy, indicating disturbed emotional processing. 59 However, fibromyalgia, which most closely resembles somatoform pain disorders in many aspects, displays a characteristic connectivity pattern during rest, as recently shown by Cifre and colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, noxious heat led to higher blood oxygen-level dependent signalling in the insula and parahippocampal gyrus, while medial prefrontal cortex activity was reduced. 58 Reduced insula and amygdala activity was observed during emotional empathy, indicating disturbed emotional processing. 59 However, fibromyalgia, which most closely resembles somatoform pain disorders in many aspects, displays a characteristic connectivity pattern during rest, as recently shown by Cifre and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high comorbidity of somatoform pain with affective disorders 61 and their influence on brain function, 58,62 depressive symptoms may have influenced our results. Several studies have indicated an important role of functional connectivity in depressive symptoms.…”
Section: Limitationsmentioning
confidence: 99%
“…Many studies have found parahippocampal activation in response to pain (22), where it is believed to mediate the aversive drive and contribute to the negative affect inherent to pain. Interestingly, parahippocampal responses to pain are shown to be increased by anxiety in healthy volunteers (13), as well as in clinical populations suffering from anxiety-related pain disorders (23).…”
Section: Discussionmentioning
confidence: 99%
“…Even if cortical pain pathways are well explored, there are surprisingly few neuroimaging studies that directly address the influence of emotions on pain. Studies employing functional magnetic resonance imaging have revealed that the entorhinal cortex of the left hippocampal formation, the perigenual cingulate cortex and the mid-insula show increased activity when painful stimulation was administered after induction of negative emotions [23], and these regions amplify pain experience in chronic pain patients with depression [24,25]. Trait-like individual differences in pain-related fear might also have an impact on neural processing of pain.…”
Section: The Neurobiology Of Emotional Modulation Of Painmentioning
confidence: 99%